IMPLEMENTASI QANUN NOMOR 6 TAHUN 2018 TENTANG RANCANGAN PEMBANGUNAN JANGKA MENENGAH DAERAH KABUPATEN BENER MERIAH - Husnainy, Anshar; Rasyidin, Rasyidin; -, Akmal (Program Magister Administrasi Publik, 2022)
This study investigates the implementation of the Bener Meriah Regency Qanun Number 6 of 2018 concerning the Regional Medium-Term Development Plan in Bener Meriah Regency by BAPPEDA in 2019. The study's goal is to learn how the RPJMD Qanun is implemented and what challenges it faces. The theoretical perspectives used are public policy theory, policy implementation, regional development planning, supervision, politics, and bureaucratic processes. A qualitative research method was used. The results show that the RPJMD Qanun has been implemented for three years and is still not being implemented effectively and efficiently due to the development programs included in the regional medium-term development planning (RPJMD) list, experiencing changes in the stages of implementation, and the availability of the development implementation. budget in the SKPK provided Government of Bener Meriah. Obstacles to BAPPEDA Bener Meriah Regency's Role in RPJMD Implementation Qanun are caused by political obstacles in the form of political intervention by power holders, economic obstacles in the form of limited budget availability, and institutional weaknesses in the form of insufficient supervision and evaluation carried out by BAPPEDA to all SKPK related to the implementation of non-physical development programs that proved to be ineffective and underwent several changes that were not in accordance with development planning.